VD_FINDINFO Décision / 2011 / 243 vom 11. März 2011 - VD Tribunal cantonal (2011)
CLASSEMENT DE LA PROCÉDURE, NON-LIEU, EXEMPTION DE PEINE, ACTION PÉNALE | 54 CP, 319 CPP (CH), 393 al. 1 let. a CPP (CH)